Cap-Haïtien versus Jacmel, essai sur la ville en Haïti - Isabelle Duhau; Jean Davoigneau (Études Caribéennes, 2018)
In a few years between them, the two Haitian harbor towns of Cap-Haitian and Jacmel benefitted from a very detailed heritage inventory concerning buildings located in their historical center, which allows some comparisons. In the north of the island on the Atlantic coast, Cap-Haitian was the main and the richest city in the French West Indies during all the colonial period. While Jacmel, a seaside town located in the south on the Caribbean Sea, remained a modest trading post, before experiencing a period of glory, after the independence by becoming the capital of Haitian coffee. To these peculiar stories, we may add specific geographical contexts that have produced very different town planning with contrasting road layouts. It is also in the architecture of their buildings that the two cities express their peculiarities: different sourcing and use of materials, building design, interaction with public spaces and different architectural models. However, for a few years, a perception without nuance of the Haitian urban phenomenon and a new architecture have settled on the outskirts but also replacing the traditional houses in the heart of the old centers, have threatened in the long term the heritage specificities and the uniqueness of these urban spaces.